An extension to classical lamination theory for use with functionally graded plates. - Reid, R.G.; Paskaramoorthy, R. (Elsevier, 2011)
An extension to classical lamination theory is presented for the improved analysis of thin to moderately thick functionally graded plates. The method results in an explicit formulation that accommodates any through-thickness variation in the elastic, hygrothermal and piezoelectric properties of each layer. Additionally, variations in the material rotation angle, temperature, moisture content and electric field strength through each layer are taken into account. The method relies on representing with polynomial series the variation in both the properties of each ply and the hygrothermal and piezoelectric loading. Validation problems are presented that demonstrate the application and accuracy of the method.
Keywords: Lamination theory; Functionally graded materials; Analysis; Electric field strength; Explicit formulation; Hygrothermal; Piezoelectric property; Polynomial series